Polycyclic polyprenylated acylphloroglucinol derivatives from Hypericum pseudohenryi. (July 2021) - Sun, Haoran; Wang, Jiajia; Zhen, Bo; Wang, Xue; Suo, Xinyue; Lin, Mingbao; Jiang, Jiandong; Ji, Tengfei
Abstract: Seven previously unidentified polycyclic polyprenylated acylphloroglucinol (PPAP) derivatives hypseudohenrins A–G, along with six known analogs, were isolated from the aerial portion of Hypericum pseudohenryi . Their structures were determined by NMR, ECD and X-ray crystallographic spectroscopy. These compounds were screened for anti-inflammatory activity, and hypseudohenrins B and G (at the concentration of 10 μM) showed NO production inhibition ratios of 52.56% and 54.01%, respectively, which imply good anti-inflammatory activity. In particular, uraloidin A exhibited an NO inhibition ratio of 90.61%, while that ratio of the positive control compound dexamethasone was 94.88%. Additionally, anti-cancer and neural-protective activities were screened, but none of these compounds showed desirable activity. Graphical abstract: Image 1 Highlights: Seven new polycyclic polyprenylated acylphloroglucinol derivatives, hypseudohenrins A–G, were isolated. Hypseudohenrins A and B bore a 6/6/5/6 ring system, their biosynthetic precursors were also obtained. The biosynthetic pathways of hypseudohenrins A–E were proposed. Hypseudohenrins F and G were a pair of epimers, and hypseudohenrin F was obtained as colorless crystal. The absolute configurations of all new compounds were identified.